2012
DOI: 10.1371/journal.pntd.0001689
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and Specific Detection of Trypanosoma cruzi DNA in Clinical Specimens Using a Multi-Target Real-Time PCR Approach

Abstract: Background The laboratory diagnosis of Chagas disease is challenging because the usefulness of different diagnostic tests will depend on the stage of the disease. Serology is the preferred method for patients in the chronic phase, whereas PCR can be successfully used to diagnose acute and congenital cases. Here we present data using a combination of three TaqMan PCR assays to detect T. cruzi DNA in clinical specimens. Methods/Principal Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
90
1
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 35 publications
3
90
1
9
Order By: Relevance
“…Although the parasite burden was nonquantifiable in this study, parasite DNA was found in the peripheral blood of all groups of chagasic patients, indicating parasite persistence. During chronic infection, the parasite remains in tissues, such as the heart and other reservoir tissues (94)(95)(96)(97); thus, the parasite load in the blood is low or not detectable in some patients. Indeed, the antigenic load is an important difference between viral and parasitic models of CD8 + T cell dysfunction.…”
Section: Cd8mentioning
confidence: 99%
“…Although the parasite burden was nonquantifiable in this study, parasite DNA was found in the peripheral blood of all groups of chagasic patients, indicating parasite persistence. During chronic infection, the parasite remains in tissues, such as the heart and other reservoir tissues (94)(95)(96)(97); thus, the parasite load in the blood is low or not detectable in some patients. Indeed, the antigenic load is an important difference between viral and parasitic models of CD8 + T cell dysfunction.…”
Section: Cd8mentioning
confidence: 99%
“…Microscopy and PCR-based methods are more effective for diagnosing acute or congenital forms of Chagas disease (14,15), while serological tests using either parasite-derived antigens, recombinant proteins, or synthetic peptides are preferred for diagnosis of chronic infections (16). Despite the sensitivity of serological tests, current Chagas disease diagnostic tests may lack specificity due to cross-reactivity with the related parasites Leishmania spp.…”
mentioning
confidence: 99%
“…However, it must be underlined that the validity of molecular and parasitological methods relies on the positive results they can give, and accordingly they have been proposed for earlier assessment of treatment failure of treated chronic Chagas disease patients (15). T. cruzi contains nuclear DNA and kinetoplast DNA (kDNA), both of which contain many repetitive sequences that are highly suitable for sensitive PCR detection due to their high copy numbers (16,17). Other parasitological methods, such as the classical XD method (18), even though of much less sensitivity than PCR, are still useful in combination with PCR (19,20).…”
mentioning
confidence: 99%